Abdominal Aortic Aneurysm: Can the Anaconda™ Custom-Made Device Deliver? An International Perspective - Jubouri, Matti; Surkhi, Abedalaziz O.; Tan, Sven Z. C. P.; Bailey, Damian M.; Williams, Ian M.; Bashir, Mohamad (Frontiers in Cardiovascular Medicine, 2022)
Since the introduction of endovascular aortic repair (EVAR) it has demonstrated excellent clinical outcomes and has replaced open surgical repair (OSR) in the treatment of abdominal aortic aneurysms (AAA). AAA is a life-threatening abnormal dilation of the abdominal aorta to 1.5 times its normal diameter. Several commercial EVAR devices exist on the global market, with the Terumo Aortic Fenestrated Anaconda™ graft showing superiority. In the current study, we sought to provide an international perspective using multicentre-multinational data on the Anaconda™ device characteristics, design, and delivery, and discuss relevant literature. The current study represents a cross-sectional international analysis of custom-made fenestrated Anaconda™ device. Ethical and legal approval for data collection was obtained from each of the local authorities. For the statistical analysis, SPSS 28 for Windows and R were utilised. Pearson Chi-Square analysis was used to assess differences in cumulative distribution frequencies between select variables. Statistical significance for all two-tailed tests was set at p <0.05. A total of 5030 Anaconda™ devices were implanted during the 9-year study period in 27 countries spanning 6 continents. The predominant device category was bifurcate (83.6%), whilst the most common proximal ring stent configuration being standard (64.5%). All devices were delivered within 8 weeks of diagnosis, with most being implanted within 6-8 weeks (55.4%). The Anaconda™ was indicated in the 3891 (77.4%) patients due to competitor rejection/inability to treat unsuitable/complex aortic anatomy. In the remaining 1139 (22.6%) patients, it was utilised based on surgeon preference. Almost all devices (95%) were delivered along with a prototype. Of the total 5030 Anaconda™ devices, 438 (8.7%) used 0-1 fenestrations, 2349 (46.7%) used 2-3, while 2243 (44.6%) utilised 4,5 or 6 fenestrations. The Terumo Aortic Fenestrated Anaconda™ device features a highly unique and innovative design which enables it to treat highly complex aortic anatomy while achieving excellent results. Additionally, the Anaconda™’s custom-made approach allows it to be tailored to individual patient anatomy, this in addition to the device prototype provided by Terumo Aortic optimise clinical outcomes. Finally, the Fenestrated Anaconda™ is a highly versatile device offering a wide range of device categories, configurations, and sizes.